Vitiligo-Like Depigmentation following Treatment with Imiquimod 5% Cream for Condylomata Acuminata - Maram Alatabani; Yasser Ghobara; Ahmed Alissa (Karger Publishers, 2021)
Imiquimod cream is an immunomodulatory agent that has been approved by the US Food and Drug Administration for use in the treatment of anogenital warts (condylomata acuminata) due to its local immune effects in activating Toll-like receptors 7 and 8 on antigen-presenting cells, resulting in reduction of the viral load of human papillomavirus with subsequent wart regression. After its application, some side effects are commonly reported, including erythema, edema, scaling, erosion, and ulceration. While pigmentary changes, including vitiligo-like depigmentation, have been mentioned as a possible side effect, they have rarely been reported in the literature. Alterations in pigmentation occur because imiquimod application causes human melanocyte apoptosis and autodestruction resulting in loss of melanocytes. Herein, we report the rare case of a 34-year-old healthy male who developed vitiligo-like depigmentation following imiquimod application for his genital warts. This case report aims to increase physicians' awareness of this possible side effect that could be irreversible and difficult for the patient to accept.